The involvement of Ex-Military commissioners and the selection of industry specialist auditors - Ilhamda Azis; Iman Harymawan; Mohammad Nasih (Cogent Business & Management, 2022)
This study aims to examine the relationship of military connections in the form of company commissioners with retired military backgrounds to the selection of industrial specialist auditors. The sample selection technique we use is a purposive sampling technique with several criteria. This study uses a sample of 618 public companies listed on the Indonesia Stock Exchange from 2016-2018. This study employs logistic regression analysis used through the STATA 14 application to test the hypotheses. This study found that companies with retired military commissioners had a significant positive effect on the selection of industrial specialist auditors. This research contributes to the literature on military connections and the selection of industry specialist auditors, especially in Indonesia.
Keywords: 650; board commissioners; good governance; industrial specialist auditors; military commissioners; military connections